The Emerging Role of Arginase in Endothelial Dysfunction in Diabetes - Pernow, John; Jung, Christian (Current Vascular Pharmacology, 2016)
Diabetes mellitus is a major risk factor for the development of cardiovascular disease due to increased vascular inflammatory and oxidative stress favouring atherogenesis. Endothelial dysfunction has received increasing attention as a potential contributor to the pathogenesis of vascular disease in diabetes mellitus. Although the underlying cause of endothelial dysfunction is multifactorial, a key factor is impairment of the bioavailability of nitric oxide (NO). Emerging evidence suggest that upregulation of arginase is of central importance for reduced NO bioavailability due to competition for the substrate L-arginine between arginase and the endothelial form of NO synthase. Arginase is also associated with increased oxidative stress, further impairing NO bioavailability. Upregulation of arginase has been suggested to be a key factor driving endothelial dysfunction in diabetes. The present review describes the regulation of arginase in relation to diabetes and arginase as a potential therapeutic target to improve endothelial function in experimental models and the clinical setting of diabetes mellitus.
Keywords: oxidative stress